Guitarra Negra : A journey through a collaborative creative process - Caldas Zeballos, Sebastián (2012)
Guitarra Negra, a journey through a collaborative creative process, is an artistic research project that tries - through qualitative research methods - to decode the essence in collaboration between a composer and a performer in their attempt to create and record a musical work. The premises of the project were to create a fusion of contemporary western music and flamenco in a piece for guitar solo and chamber ensemble. It was decided at the outset that the project would also explore the possible dynamics of the interrelation between composer and performer. The collaborative process is analyzed with tools derived from a review of analytical models and theories of collaboration. Since the collaboration involved the transmission and transformation of musical traditions the research demanded a historical review of flamenco and its evolution as well as a discussion of the theory on how musical traditions are created and transformed. I also discuss the process of critical editing of the guitar part and how the interaction between composer, score, and interpreter works in the negotiation of a final version for the recording. The last chapter of the collaboration involved the making of the recording, which implied a “collaboration in the collaboration” which is analyzed with the same tools used when reviewing the interaction between composer and performer. The artistic result is a CD recording of the work Guitarra Negra for guitar and sextet (fl. cl. piano, percussion, vl. vc.) recorded at Studio Acusticum in Piteå and released by Daphne Records. Validerat; 20120926 (anonymous)